A new river loach from the main channel of the upper Mekong in Yunnan (Cypriniformes: Nemacheilidae) - Endruweit, Marco; Yang, Junxing; Liu, Shuwei (Zootaxa, 2016)
Nemacheilid loaches are a common element of fish assemblages of Southeast Asian streams. In particular, streams in tropical and subtropical regions with a gravelly to rocky substrate and a swift current are typically inhabited by several species of nemacheilid loaches. Up to six different species are reported to occur syntopically (Kottelat 1990). The vast majority of these loaches are allocated within the diverse genus Schistura, which accommodates about 200 valid species (Kottelat 2012). River loaches of the genus Schistura are defined as having the mouth moderately arched; the lower lip medially notched, not forming lateral labial pads; air bladder without a secondary chamber, and a maximum size between 25 mm and 120 mm SL (Kottelat 1990).